Labor market rigidity and the success of economic reforms across more than one hundred countries - Forteza, Alvaro; Rama, Martâin 1956-.; World Bank. (Washington, D.C. World Bank, 2001)
Labor market policies and institutions affect the success of economic reform but probably more for political than for economic reasons. Growth appears not to be hurt by minimum wages and mandatory benefits. But the relative size of organized labor (in government and elsewhere) is crucial.
Keywords: Economic development -- Effect of Labor market on; Manpower policy -- Economic aspects -- Econometric models; Labor unions -- Econometric models